Extensor Pollicis Brevis Transfer to Extensor Pollicis Longus for Delay Spontaneous Ruptures: A Case Series and Functional Outcomes at One Year Follow Up - G, Kastanis; P, Kapsetakis; C, Chaniotakis; I, Stavrakakis; A, Pantouvaki (International Journal of Innovative Research in Medical Science, 2022)
Introduction: When Extensor Pollicis Longus (EPL) spontaneously ruptures, two major risk factors are present: rheumatoid arthritis and distal radius fracture. The gold standard treatment is the transfer of Extensor Indicis Proprius (EIP) to restore the functionality of the thumb. Utilization of Extensor Pollicis Brevis (EPB) was used initially, in patients with rheumatoid arthritis. The aim of this study is to ascertain if the EPB transfer technique is the most competent and efficient surgical method for rupture of EPL, analyzing functional outcomes, complications and final patient`s satisfaction. Material & Methods: Eighteen patients (14 female and 4 men) with an average age of 43 years old were introduced in this study. All cases reported no history of trauma. From the derived clinical history, 8 cases suffered from rheumatoid arthritis, 4 patients reported initial corticosteroid injection in radial side of wrist, one case was revised surgery and in rest cases the etiology was unknown. Radiographic investigation was normal in all cases, while magnetic resonance studies detect EPL ruptures. All patients were operated in a mean time of 3, 4 weeks (ranging from 2 to 6 weeks) after the diagnosis and in all cases the tendon applied was the EPB. After surgery all patients followed the same rehabilitation program. Results: The mean follow-up was 20,5 months (range from 15 months to 36 months). None of patients missed the last re-examination. Results were evaluated according to complications, range of motion of the thumb (elevation deficit, opposition distance, difference flexion-extension deficit), Quick Dash Score, EQ-5D-5L, and satisfaction of the patients. No intra-or extra-operative complications or re-ruptures were noted. At the final follow up the mean range of elevation deficit was0,7(from 0,5 to 1,5), opposition distance was 0,8(range from 0,5 to 1,8) and difference flexion-extension deficit was 1,6˚ (from 0˚ to 5˚). The Quick Dash score was 1.38 (varied from 0.0- 6.8) and the EQ-5D-5L was 92. Finally, the majority of patients appeared to be very satisfied (66,7%) or satisfied (27,8%). Conclusion: Extensor Pollicis Longus tendon spontaneously ruptures due to specific factors. Restore of thumb functionality is achieved only with tendon transfer technique and the use of Extensor Indicis Proprius tendon has been described as the gold standard. Extensor Pollicis Brevis tendon transfer is an alternative technique with significant advantages which preserves good functionality of the thumb and excellent patient satisfaction.